THE PUBLIC ACCOUNTANT, MANAGER OF STRATEGIC INFORMATION IN INTERNATIONAL BUSINESS: PERU AND ASIA PACIFIC - Choy Zevallos, Elsa Esther (2012)
Business relationships with Asia Pacific are recording significant increase, which represents development opportunities for Peru, if you consider that the next twenty years; China could become the world’s largest economy. There is certainly potential for international business, for which is essential develop and implement instruments of managerial decision making, based on the accounting and financial information. Both countries have adopted or are adopting International Financial Reporting Standards; this process involves risks in the implementation of IFRSs and in the management of business information. In this international scene be make relevant the social, cultural, political and technological factors that distinguish the way of doing business in Peru of the way of doing business in China. This paper seeks to identify challenges for the accounting profession and in the management of economic, financial and strategic information, that comes from an increase in international business between Peru and Asia Pacific. The research design is descriptive and analytical, using information, and regulatory instruments related to international financial reporting standards and competencies.